Strategi Penguatan Usaha BUMDesa Melalui Peningkatan Kualitas Laporan Keuangan - Dina Alafi Hidayatin; Mukti Prasaja; Latifah Anom (Universitas Mercu Buana, 2022)
The government continues to make efforts to increase village development. This is evidenced by the implementation of one of the programs in the form of the establishment of Village-Owned Enterprises (BUMDes). BUMDes was established based on the principles that characterize this business unit. These principles is such as cooperative, balance, tranparansi and accounting. These principles must be implemented in financial management carried out by BUMDes. One of them happened at BUMDes in Bogo Village. This village has the uniqueness as a tourist village, namely kelor village. In the village, BUMDes is also established, Unit Dagang and Kelompok Wanita Tani (KWT) which has made financial statements. Through the qualitative approach used by the researcher and interviewing some of the information in this study, the results are obtained if in terms of transparency, the financial reports that have been prepared in each period have met transparency. This is evidenced by the financial statements that have been prepared and have been informed to the Village Head and local village officials. However, on the other hand, the financial statements they did are not comply with the standards that have been put in place by the Government. Therefore, the need to adjust the financial statements of BUMDes in Bogo Village to the standards set by the Government and the encouragement of cooperation conducted by bogo village with related agencies for the performance of BUMDes is getting better.